ASSESSMENT OF STUDENTS’ PROFESSIONAL COMPETENCIES – THE FUTURE TEACHERS OF MATHEMATICS - Mariya B. Shashkina; Ekaterina A. Ayoshina (Образование и наука)
The aim of the investigation is to describe the authors’ approach to the assessment of the professional competence of the future teacher of mathematics.Methods. The methods involve comparative analysis of the Professional Standard of the teacher and the Federal State Educational Standards in teacher education, as well as the method of predictive analysis of modern educational situation.Results. Qualimetric approach to the structuring of the professional competencies of students is described; it allows concretizing the assessment object, to select the criteria and levels of its formedness, to trace the dynamics of development in the medium of profile preparation of a bachelor. The methodology of assessment a professional-profile competence of the future mathematics teachers is proposed; examples of the competence-assessment tools are provided.Scientific novelty. The study gives a detailed analysis of developing the innovative approach to competencies assessment as metasubject learning outcomes.Practical significance. The proposed method of competencies assessment can be used in the mathematical preparation of the future mathematics teacher, and can serve as a basis for monitoring the professional competencies of students.